The Banana Tree at the Gate: A History of Marginal Peoples and Global Markets in Borneo - E. N. Anderson (Ethnobiology Letters, 2012)
Review of The Banana Tree at the Gate: A History of Marginal Peoples and Global Markets in Borneo. Michael R. Dove. New Haven, CT: Yale University Press, 2011. Xix, 332 pp. Illus. Bibliography, indexes. ISBN 978‐0‐300‐15321‐7 (hardcover). $55.00.